Evaluasi Efektivitas Pemberian Kalsium dengan Metode Split-Feeding terhadap Produtivitas Puyuh Petelur: Evaluation of The Effectiveness of Calcium Administration with Split-Feeding Method on The Productivity of Laying Quail - Binowo, Seruni; Sumiati; Mutia, Rita (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
High-productivity laying poultry during the production period may experience bone problems, as structural medullary bone is progressively absorbed to supply calcium for eggshell formation. This study aims to evaluate the usage of different particle sizes of limestone (fine (0,025mm), and coarse (1mm)), and split feeding system (morning (8 am) and afternoon (15 pm)) on laying quail productivity. This research used 160 quail aged 18 weeks, which is reared up to 23 weeks. A complete randomized design (CRD) with 4 treatments and 4 replicates was used in this study. Each replicate consisted of 10 quails. The cages used were multilevel colonies equipped with feed and drink containers. The diet treatments were: P0= diet contained fine (FL) and coarse (CL) limestone at a (25:25): (25:25) ratio fed in the morning and afternoon, P1= diet contained 75FL-(Morning): 25CL-(Afternoon), P2= diet contained 50FL-(Morning):50CL-(Afternoon) and P3= diet contained 25FL-(Morning):75CL-(Afternoon). Data were analyzed using ANOVA and further analyzed using the Duncan test. The results showed that the ration treatment with limestone divided into fine and coarse forms with split feeding in the morning and evening significantly increased (p<0.05) tibia bone Ca and P content but decreased (p<0.05) feed conversion. However, it increased (p<0.05) quail egg index value. Feeding calcium at a ratio of 25% (morning) and 75% (afternoon) resulted in the highest ration utilization efficiency, Ca and P deposits in the tibia bone, and increased egg index values. Key words: Ca and P medullary bone, calcium effectivity, eggs quality, performance, quail laying